EFFECT OF CLEANING EFFICIENCY OF DIFFERENT SELECTION VARIETIES OF COTTON PRIMARY WORKING PROCESS AND INFLUENCE ON SEED CONTAMINATION AMOUNT - Yuldasheva , M.T.; Yodgorov, S.; Kulmetov, M.; Ochilov, T.A. (Educational Research in Universal Sciences, 2024)
in this article, it was conducted in "ZAMIN ANGOR CLUSTER" LLC and "SAX CLUSTER" cluster system enterprises in Surkhandarya region. For him, the efficiency of cleaning from small and large impurities of promising selection varieties Termez-49, Surkhan-101, Surkhan-9, Termez-208 and Surkhan-102 grown in some farms of Denov and Shorchi districts was studied in the laboratory of the enterprise in the cluster system